HUBUNGAN SELF-EFFICACY DENGAN KECEMASAN DALAM PROSES PEMBELAJARAN MAHASISWA SEMESTER II FIKES UNIVERSITAS MUHAMMADIYAH TANGERANG - Nuraeni, Een; Akhmad, Shieva Nur Azizah; Wijoyo, Eriyono Budi (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2021)
ABSTRACTOnline learning causes a lot of conflicts, one of which is anxiety and makes students' self-efficacy decrease. The age of the second semester students is still classified as a teenager, therefore they are not emotionally stable. So that it can be affected by anxiety and self-efficacy. This study aims to determine the relationship between self-efficacy and anxiety levels. The type of research used is quantitative research. The sample of this study were all students of the second semester of the UMT nursing study program as many as 71 respondents. The data analysis method in this study consisted of univariate analysis to determine the frequency distribution of each variable. Bivariate analysis was carried out to analyze the independent variables suspected to have a relationship with the dependent variable using the Chi Square test (continuity correction) and the calculation of the Odd Ratio (OR). . The research results obtained were yielding (p = 0.006) and OR 0.01. The conclusion of this study is that there is a relationship between self-efficacy and anxiety levels. Suggestions in this study for related parties in learning in order to modify the systematics in the learning process so that students do not experience anxiety. ABSTRAKPembelajaran daring banyak menimbulkan konflik, salah satunya adalah kecemasan dan menjadikan self efficacy pelajar menurun. Usia mahasiswa semester II masih tergolong remaja, maka dari itu emosionalnya belum stabil. Sehingga dapat terpengaruhi kepada kecemasan dan self efficacynya. Penelitian ini bertujuan mengetahui hubungan antara self efficacy dengan tingkat kecemasan. Jenis penelitiain yang digunakan adalah penelitian kuantitatif. Sampel penelitian ini yaitu semua mahasiswa semestrer II prodi keperawatan UMT sebanyak 71 responden. Motode analisis data dalam penelitiain ini terdiri dari analisis univariat untuk mengetahui distribusi frekuensi dari masing-masing variable, Analisis bivariat dilakukan untuk menganilisis variabel independen yang diduga mempunyai hubungan dengan variabel dependen dengan menggunakan uji Chi Square (continuity correction) dan perhitungan Odd Ratio (OR). Hasil penelitian yang diperoleh secara menghasilkan (p=0,006) dan OR 0,01. Kesimpulan penelitian ini yaitu ada hubungan antara self efficacy dengan tingkat kecemasan. Saran dalam penelitian ini untuk pihak terkait dalam pembelajaran agar dapat memodifikasi sistematika dalam proses belajar supaya mahasiswa tidak mengalami cemas.